Northwest History. Alaska. Earthquakes & Volcanoes. (1937)
Earthquakes In Alaska Create Tense Feelings. Earthquakes in Alaska Create Tense Feelings FAIRBANKS, Alaska.— — Earthquakes which rocked the east central area of Alaska, from Fairbanks to the south coast, left residents apprehensive and nervous today. The first tremor early Thursday was followed through the day by a series of minor shocks. The Black Rapids glacier, southwest of here, which for a time last winter was moving down the valley at the unprecedented rate of two miles a month, was reported jarred into renewed activity by the tremor. No deaths were reported.